An Expedient Synthesis of 2-Aryl-substituted 2,3-Dihydroquinazolin-4(1H)-ones in Low Transition Temperature Mixture (LTTM) containing SnCl2 and L-Proline - Desai, V.M.; Birajdar, A.T.; Patil, S.P.; Kupwade, R.V.; Deshmukh, M.B.; Patil, S.S. (Asian Journal of Chemistry, 2022)
2,3-Dihydroquinazolin-4(1H)-ones were synthesized in excellent yield in a prepared low transition temperature mixture (LTTM) containing SnCl2 and L-proline using either direct one-pot two-component cyclocondensation of anthranilamide and aldehydes or one-pot three-component cyclocondensation of isatoic anhydride, ammonium acetate and aldehydes. The prepared LTTM is a green solvent, inexpensive, non-toxic and serves a dual function as reusable catalyst and solvent with excellent reaction endorsing medium. The current protocol has several advantages including an easy work up, shorter reaction time, high yield with a higher atom economy and maximum reaction efficiency with excellent green chemistry metrics.